Distance Education: Notes about Its Origins and Fair Value as a Practical and Powerful Resource for Permanent Education in Light of Intergenerational Change - Ruiz Badilla, Silvia (2009)
Education is a continuous and permanent process that aims to gradually bring human beings closer to perfection while allowing them to project themselves on the individual and social planes, with the ultimate purpose that such fulfillment and perfection contribute to the progress of people around them, their community, and society in general.